UNDERGRADUATE STUDENTS’ EXPERIENCES ON ONLINE LEARNING DUE TO COVID-19 PANDEMIC: THE INFLUENCE OF ENGAGEMENT AND PEDAGOGICAL CHARACTERISTIC IN EFL CONTEXT - Kardi Nurhadi; Sister Ninda Putri; Atikah Wati (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
This study is aimed to report undergraduate students’ experiences on online learning due to the Covid-19 pandemic. While online learning is not new, this was a novel and sudden experience for students who normally attend school, relatively little empirical evidence explore how undergraduate students experience during online learning due to the Covid-19 pandemic in terms of their engagement and pedagogical aspects. To fill this gap, this present study focused on investigating undergraduate students' experience of online learning in engagement included students’ active involvement category and pedagogical characteristics such as personalization, authenticity, and collaboration. Grounded in qualitative approach with phenomenological case study design. Out of thirty-one undergraduate students of 2nd semester major in English education in one of universities in West Java, three undergraduate students were recruited as the participants voluntarily in this study. The data were collected from online interviews adopting the three-interview series framework by Seidman’s (2013) consisting of thirteen questions. The data were qualitatively analyzed by inductive phenomenological reduction from Seidman’s (2013). The result of this study showed two emergent findings on undergraduate students' experience during online learning. First of all, the term of engagement on online learning of undergraduate students shows that each participant has a wide range of class involvement. Secondly, the pedagogical characteristic of personalization aspect indicated that students have independent learning such as read repeatedly the material and access more than one learning source.